If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) + -1(3x + -5) = 0 Reorder the terms: 2(3 + x) + -1(3x + -5) = 0 (3 * 2 + x * 2) + -1(3x + -5) = 0 (6 + 2x) + -1(3x + -5) = 0 Reorder the terms: 6 + 2x + -1(-5 + 3x) = 0 6 + 2x + (-5 * -1 + 3x * -1) = 0 6 + 2x + (5 + -3x) = 0 Reorder the terms: 6 + 5 + 2x + -3x = 0 Combine like terms: 6 + 5 = 11 11 + 2x + -3x = 0 Combine like terms: 2x + -3x = -1x 11 + -1x = 0 Solving 11 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 0 + -11 -1x = 0 + -11 Combine like terms: 0 + -11 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| x^6-152x^3+3375=0 | | 12x-9/3= | | 8x-4(6x+1)= | | 16x^2-16x+2.56=0 | | 8a-14b= | | 4x+2(3x-2)= | | 3x-6y=8 | | 8+2x-5-3x= | | 2m+24= | | 36-19x=-6x+41 | | -5(-9a-8b+2)= | | 3-3y^2=0 | | -9(n-1)= | | 3(m-2)= | | -3/2*5= | | 4-(9-8x)+3x=x+10 | | -X-2Y=-8 | | 16x^2-49-87=0 | | 42=3x-15 | | (4+X)(5X+9)=0 | | x^4+80x^2+1024=0 | | 2y-6x=15 | | 7+47z=14z^2 | | 25x^2+12x-15=0 | | 29x-10-13x=4(4x-3)+2 | | 7+44z=35z^2 | | x+250=2x | | 12.50n+35=15.00n+22.50 | | 1.25r+37=2.00r+19 | | 5a+1=a+1 | | x^2=81x | | 8(x-6)=5 |